Straight Two-Points Distance Calculation in 3D Space Using Midpoint Proximity of Stereo Image - Saputra, Efa Maydhona; Hidayat, Risanuri; Bejo, Agus (2022)
This paper provides straight two-points distance calculation method in 3-dimensional space using stereo image. The images are taken by two identical camera which 10cm apart. Both camera's point of views is parallel to each other. A center vertical line and center horizontal line are added to each image. Each interest point on interest object are marked. To increase the accuracy, each point chooses their parents by choosing the closer midpoint stereo image. The distance calculation adopts Euclidian distance with combination of two images, while the previous method only uses single image for reference. This paper presents the comparison of our work with previous work using our data. The results show that distance calculation using previous method on right image make an error around 3,5, using previous method of left image make an error around 3,45, and our method make an error around 2,62. It proves that our method is slightly better than the previous one. © 2022 IEEE.